Removal of Azoxystrobin and Deltamethrin from Water Using Activated Biochar from Moringa oleifera L. Wood: Synthesis, Characterization, and Adsorption Study - Hiago Gomes; Ellen Bento; Maria Dayrine Tavares; Yannice Santos; José Galberto da Costa; Ronaldo do Nascimento; Stefano Salvestrini; Raimundo Teixeira (Molecules)
The aim of this study was to evaluate the efficiency of activated biochar produced from Moringa oleifera L. wood for removing azoxystrobin (fungicide) and deltamethrin (insecticide) from water. The adsorption of pesticides on activated carbon was studied using batch tests evaluating the influence of contact time (1–180 min), concentration (5–50 mg L−1), and temperature (283, 298 and 313 K). The highest removal percentage obtained was 94.39% for azoxystrobin and 91.96% for deltamethrin, considering an initial concentration of 10 mg L−1 and adsorbent dosage of 5.0 g L−1. FTIR spectra confirmed H-bonding in the adsorption process, SEM analysis revealed homogeneous surface area characteristics, and BET results confirmed a highly superficial area for the activated carbon, all of which favor pesticide adsorption. The Boyd model showed that the intraparticle diffusion stage is determinant for both compounds in the initial stages of the adsorption process. The Sips model was the isotherm with the best fit to the experimental data, possibly indicating cooperativity between adsorbate molecules at low temperatures. The thermodynamic study showed a favorable adsorption at all the temperatures investigated, given the negative value of ΔG°. In addition, this study revealed good adsorption capacities for the material indicating that Moringa oleifera wood activated carbon is a viable alternative for removing azoxystrobin and deltamethrin from water.